1997
DOI: 10.2116/analsci.13.109
|View full text |Cite
|
Sign up to set email alerts
|

Is Higher Concentration of Linear Polyacrylamide Not Suitable for the Capillary Electrophoretic Separation of Large DNA?

Abstract: Polyacrylamide is an excellent separation matrix for capillary electrophoresis 110 and conventional gel electrophoresis,11,12 Low crosslinked polyacrylamide gel and linear polyacrylamide gave an excellent resolution of double-stranded DNA fragments using capillary electrophoresis. l-4,9,10 Linear polyacrylamide has been used as a separation matrix for DNA sequencing especially for long reading by capillary electrophoresis.5-gIn our common knowledge, higher concentration of polyacrylamide is suitable for separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…For linear DNA we found that for all LPA M w investigated the linear DNA conformation changed from dominant U-to I-shape as LPA concentration is increased as reported earlier (see Fig. 8c-d) [40,43]. We have also found that the concentration around which the transition from U-to I-shape conformation is induced decreases with increasing LPA M w (see Fig.…”
Section: Videomicroscopysupporting
confidence: 85%
See 3 more Smart Citations
“…For linear DNA we found that for all LPA M w investigated the linear DNA conformation changed from dominant U-to I-shape as LPA concentration is increased as reported earlier (see Fig. 8c-d) [40,43]. We have also found that the concentration around which the transition from U-to I-shape conformation is induced decreases with increasing LPA M w (see Fig.…”
Section: Videomicroscopysupporting
confidence: 85%
“…Furthermore, the transition from U-dominant to I-dominant conformations observed (around E < 15 V/ cm for all 2% w/v LPA solutions) produces no noticeable change in the field-dependence of the mobility. Ueda and Baba [40] reported a similar observation, namely that the electrophoretic mobility of linear DNA changes little when it undergoes a transition from U-to I-dominant conformations during electrophoresis. These results are evidently similar to our previous observation that conformation differences between electrophoresing star-branched and linear DNA have at most a negligible effect on mobility in unentangled LPA solutions.…”
Section: Effect Of Electric Fieldmentioning
confidence: 67%
See 2 more Smart Citations
“…x b , the presence of reptation-type migration in highly entangled solutions was strongly supported by a series of videomicroscopy studies of the motion of large DNA molecules [113][114][115][116].…”
Section: Discussionmentioning
confidence: 99%